GC-MS Analysis of Methanolic Extract of Colpomenia Sinuosa (Mertens Ex Roth) Derb. Et Sol. From Manapad in the South East Coast of Tamil Nadu, India - Ponnudurai, G.; Peter Paul, J. John (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: The present study was carried out to explore the various secondary metabolites and bioactive compounds present in the methanolic extract of brown marine macro alga Colpomenia sinuosa (Mertens Ex Roth) Derb. Et Sol. Design: The plant materials were collected from Hare Island, located in Thoothukudi, Tamil Nadu, India. The characterization of biochemicals was carried out using GC-MS analysis. Intervention: Among the different solvent extracts, methanolic extract was intervened in the present study Main outcome measure: The main measurement results in the study were to predict the presence of various phytochemicals in the methanolic extract of Colpomenia sinuosa (Mertens Ex Roth) Derb. Et Sol. Results: The analysis revealed seventeen bioactive compounds such as z,z-6,28-Heptatriactontadien-2-one (25.88%), 2-Hexadecanol (2.18%), L-(+)-Ascorbic acid (25.13%), N-propyl 11-octadecenoate (9.41%), 3-Methyl-2-(2-oxopropyl)furan (2.02%), Hexadecane (1.01%), Hentriacontane (9.00%), Palmitaldehyde (4.22%), Tritetracontane (2.42%), Squalene (1.03%), Trans-5-Hexyl-1,4-dioxane-2-carboxylic acid (4.12%), Methyl 2-hydroxy-eicosanoate (3.25%), Cyclopentane,1,1,3-trimethyl- (2.15%), Palmitoleic acid (1.64%), Vitamin E (0.18%), 2-Pentacosanone (0.22%) and 3-Methylene-1-oxa-spiro[3,6]decane (0.14%). Conclusion: The bioactive compounds from methanolic extract of Colpomenia sinuosa (Mertens Ex Roth) Derb. Et Sol. may have the potential effect against various diseases.